FLIPPED CLASSROOM: EFL STUDENTS' PERCEPTIONS OF USING INSTAGRAM REELS TO BOOST SELF-CONFIDENCE IN SPEAKING SKILLS - Muhalida Zia Ibhar; Ari Supriadi; Sofia Bella; Meisya Herdi Putri (CV. ADIBA AISHA AMIRA, 2025)
The integration of mobile-assisted language learning (MALL) with EFL, Flipped Classroom, Instagram Reels, MALL, Speaking Confidence. flipped classroom strategies offers opportunities to strengthen English as a Foreign Language (EFL) learners’ speaking confidence. This study examines the use of Instagram Reels as an additional medium to support speaking practice among first- semester Public Administration students at STIA Lancang Kuning, Indonesia. Thirty students were selected purposively to participate in this qualitative descriptive study. Data were gathered through semi-structured interviews, classroom observations, and analysis of student-produced Reels. The learning process followed three stages: pre-class learning through YouTube videos, in-class discussions and activities, and post-class speaking tasks on Instagram Reels. Findings show that 80% of students experienced greater confidence in speaking English through repeated recording and reflection. About 75% reported higher engagement due to the creative nature of the activity, and 70% believed Reels helped them understand the material in a more engaging and relevant way. Technical challenges, such as application errors or device limitations, were reported by 60% of students but were generally manageable. Students emphasized that the combination of pre-class preparation and the informal atmosphere of social media reduced their anxiety and encouraged them to speak more frequently. This study indicates that Instagram Reels can serve as an effective platform for contextual speaking practice when integrated into a flipped classroom. Teachers are encouraged to explore similar approaches, while further research may investigate its long-term influence on oral proficiency and strategies to address technical issues.